SISTEM INFORMASI PENILAIAN KINERJA PEGAWAI PADA KANTOR KECAMATAN SUKODADI DI KABUPATEN LAMONGAN DENGAN METODE AHP DAN BOOTSTRAP - Sundiya Eryfa Diana; M Hasan Wahyudi; M Ghofar Rohman (Jurnal Teknika, 2017)
So far, the employee performance assessment at the office of sukodadi sud district in lamongan regency is conducted by the appraisal officer in coordination with the Head Office. Previously was done manual calculation without using a system. The calculation carried out in the form of determination of eligibility fulfillment of promotion of employee. Decision support systems can assist in determining assessments of employee work for the purpose of regular promotion by using a method. The existence method can be used in decision support systems such as Analytical Hierarchi Process (AHP). Systematic and appropriate in the decision-making process that is able to show the value of the competence of employees in accordance with the criteria established by the Office or decision makers based on systematic data analysis for the purpose of promotion of regular.